PENGARUH KONEKSI POLITIK, CAPITAL INTENSITY, DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE - Luthfiah Nur Khairina (2022)
This study is a quantitative study that aims to analyze the relationship between political connections, capital intensity, and the audit committee on tax avoidance. This study uses 24 samples of state-owned companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Research data is secondary data obtained from the company's annual report. This study uses panel data regression analysis as a data analysis technique. The technique for analyzing research data is using the regression model test, classical assumption test, panel data regression, and partial hypothesis testing (t statistical test). Based on the test results, it can be concluded that (1) the political connection of the board of commissioners has no significant effect on tax avoidance, (2) the political connection of the board of directors has no significant effect on tax avoidance, (3) capital intensity has no significant effect on tax avoidance, and (4) the audit committee has no significant effect on tax avoidance. Furthermore, for the results of the control variables, namely (1) Return on Assets has a significant positive effect on tax avoidance, (2) leverage has no significant effect on tax avoidance, and (3) firm size has a significant positive effect on tax avoidance.